Performance and emission analysis of mango seed biodiesel-diesel blends in a single cylinder DI diesel engine. (2021) - Venkatesh, A.P.; Kumar, M. Rajesh; Venu, Harish; Maridurai, T.; Kasinathan, D.
Abstract: An experimental study is done for evaluating the performance and emission characteristics using Mango seed biodiesel and its diesel blends in a single cylinder DI diesel engine. Experimentation were done using four blends such as B10 (10% Mango seed biodiesel + 90% mineral diesel), B20 (20% Mango seed biodiesel + 80% mineral diesel) and B100 (100% Mango seed biodiesel). In this present work, a novel study is conducted using mango seed biodiesel as a potential alternative feedstock for existing unmodified diesel engine. Results on experimentation revealed that, for B10 blend, there is a marginal cylinder pressure improvement and for B20 and B100 blend, substantial HRR improvement is observed. In terms of emissions, HC (Hydrocarbon) and CO (Carbon monoxide) emissions lowered substantially along with increase in NOx (oxides of nitrogen) and BSEC (Brake specific fuel consumption) profile. Almost all the blends other than B10 showed lowered smoke emissions throughout the engine load condition.